Optimalisasi Tumbuh Kembang Anak Baduta melalui Penguatan Keterampilan Pola Asuh Orang Tua - Heny Noor Wijayanti; Dewi Setyaningsih; Almira Gitta Novika; Siti Wahyuningsih; Tupriliany Denefi; Lestariningsih Lestariningsih; Arlensa Desepha Lentera Sinari; Nenden Delima Mustawan (Universitas Baiturrahim, 2026)
Parenting is a series of activities carried out by parents continuously in a collaborative process with their children, thus supporting optimal child growth and development. In addition to nutrition, parenting styles also significantly influence child development, as they demonstrate how parents address their children's needs. Good parenting styles are closely linked to positive child development. Parenting skills are not always easy for parents to implement. Mistakes in early childhood care can be a source of problems for children's growth and development. The purpose of this activity is to improve mothers' knowledge and skills about parenting patterns in optimizing child growth and development. In this community service, the method used is based on the problems found and then providing alternative solutions, namely counseling related to understanding parenting patterns in front of the community of Pondok Hamlet, Selomartani Village, Sleman Regency. This community service activity was carried out at the toddler posyandu with the target of mothers who have toddlers totaling 17 participants accompanied by 3 mothers of posyandu cadres. The results of this community service show that the level of understanding and knowledge of parents related to parenting patterns is still sufficient as seen from the average results of the pre-test conducted before the counseling was given, namely 54.90 and after the counseling the results increased but not significantly, namely 59.21. The conclusion from this community service activity was that parenting skills are very important for the growth and development of children, so mothers of toddlers need to be given more in-depth guidance and knowledge regarding parenting patterns.